The role of environmental awareness among the residents of the city of Duhok in the disposal of waste - ahmed Muhammad Esmail, Shaima; Muhammad Esmail, Ahmed (Academic Journal of Nawroz University, 2023)
Many countries in the world today are witnessing an exacerbation of the problem of weak environmental awareness in the way of dealing with solid waste, how to manage and treat it, and then benefit from it as an economic wealth. The city of Dohuk, as one of the cities in the Kurdistan region of Iraq, was tested to study and evaluate the extent of awareness of people and families in the city of Dohuk with waste. The main objective of the study is to evaluate the level of environmental awareness among the residents of the city of Dohuk in dealing with and disposing of waste. And knowing the most important mechanisms used by the responsible systems in the study area. The study dealt with two sections. The first section covered the theoretical aspect and presented the most important definitions of solid waste, its types, and how to deal with it. The second section includes the applied aspect. The problem of the study was the lack of environmental awareness, the lack of knowledge of the correct methods for dealing with waste and arranging it in a way that reduces the efforts made by the state to deal with it, and the lack of availability of waste transfer devices if this waste is transported directly to sanitary landfill sites. Therefore, the study assumed a low level of environmental awareness among the residents of Dohuk in dealing with and disposing of waste and how to benefit from it. The study relied on the descriptive approach and the analytical approach. As for data, the data collection process was carried out by relying on the questionnaire designated for this purpose, with (108) sample members relying on the questionnaire form. The most important statistical indicators that were chosen in testing the hypothesis are frequency and percentage. The study reached a number of results, the most prominent of which is the noticeable discrepancy in the presence of an integrated service provided by the municipality of the Dohuk region for waste collection, while there are areas that are still not served or suffer from a defect in the waste collection process, and also the lack of interest by the municipality in sorting waste for the purposes of landfilling, and in fact waste is still being collected. Mixedly, without taking into account the importance of sorting them. The study recommends several proposals, the most important of which is the necessity of holding seminars, courses, and programs for people to teach them the most important ways to properly deal with waste and how to dispose of it, in addition to the importance of adopting modern methods for landfilling waste, through which they can learn about the modern methods followed by developed countries in treating waste. Finally, emphasizing the importance of sorting waste by providing citizens with different types of waste containers suitable for sorting waste in a way that facilitates the process of recycling it later.